Spinoza: Variations on the Democratic Question (Teología, 2022)
Under a Spinozist inspiration, democracy is conceived as a regime in which the constitution, laws and procedures are institutions forged by popular life, by social struggles and collective experience, which in this way is always self-institution. This notion of democracy never presupposes mistrust of the common power, inhibition by fear, or the depoliticization of the collective body for its con opening of the political and not so much a form of government among others, the democratic question is the question of the "free multitude"
Keywords: Spinoza; Passions; Democracy; Freedom